Konsep Perencanaan Dalam Manajemen Pendidikan - Usep Suherman; Esya, Esya Mulyani; Eliva Sukma Cipta (Journal of Teacher Training and Educational Research, 2024)
Plans or planning are needed in various forms of organization, because this planning is a basic management process in making decisions and taking actions. Planning is needed in all types of activities, be it organizational activities, companies or activities in the community, and planning exists in every management function, because these functions can only carry out decisions that have been determined in planning. This article aims to reveal the importance of planning in the education management system. The research method used is a literature study. The results of this study reveal that planning is the process of defining organizational goals, producing management art to achieve goals, and planning organizational work activities. Planning is also the most important process in the principle of all management functions, because without planning other functions of organizing, directing, and controlling. Good planning will form good management. We recommend that in reaching decisions and actions in various forms of organization use the basic management process in the form of planning. In a plan, it is necessary to pay attention to the nature of good planning to achieve the desired results.